A Solvothermal Process to Synthesize Barium Metastannate Nanoparticles Assisted by Microwave Irradiation - Sung Lim, Chang (Asian Journal of Chemistry, 2012)
Barium metatstannate (BaSnO3) nanoparticles were synthesized successfully using a facile microwave solvothermal route followed by further heat-treatment. Well-crystallized BaSnO3 nanoparticles were formed after heat-treatment at 800 ºC for 3 h showing a fine and homogeneous morphology with particle sizes of 60-80 nm. The synthesized BaSnO3 nanoparticles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy and transmission electron microscopy.